Two new Cambodian semi-aquatic earthworms in the genus Glyphidrilus Horst, 1889 (Oligochaeta, Almidae), based on morphological and molecular data - Jirapatrasilp, Parin; Prasankok, Pongpun; Sutcharit, Chirasak; Chanabun, Ratmanee; Panha, Somsak (Zootaxa, 2016)
Combining morphological and molecular data is a powerful approach to support the discovery of new species. Here, two new species of the semi-aquatic earthworm genus Glyphidrilus, G. jamiesoni sp. n. and G. kralanhensis sp. n., are described from the Mekong Basin in Cambodia. They are morphologically distinguished by the respective locations of wings and spermathecae; furthermore, G. kralanhensis sp. n. has three pairs of ovaries, probably an autapomorphic trait. In addition, two mitochondrial gene fragments (COI and 16s rRNA) were sequenced of types of the new species and of five further Glyphidrilus species described recently from the Mekong basin in Thailand and Laos. They revealed a high level of genetic divergence of the new species compared to the other earthworm taxa. The evolutionary relationships among the Mekong Glyphidrilus members is discussed with reference to the recent paleogeography of the Mekong River drainage.